Do Intra-Trade Export and Foreign Direct Investment Promote Economic Growth in ASEAN? Evidence from Regional Integration - Nurjannah; Raja Masbar; M. Shabri Abd. Majid; Suriani (Proceeding of International Conference on Multidisciplinary Research, 2024)
This study aims to analyze the effect of trade between countries and foreign direct investment on economic growth in the ASEAN integration region. Elements of capital, labor, and education variables are also studied in research studies. The research data is balanced panel data in the form of ASEAN-10 from 1996 to 2021. Data analysis uses the System Generalized Method of Moments. The study's results found that labor capital, education, and intra-trade positively affected ASEAN economic growth. However, foreign direct investment has a negative effect on economic growth. A similar sign is also found in the long term, where labor capital, education, and intra-trade have a positive effect while foreign direct investment has a negative effect. Interestingly the highest effect when compared to others. Meanwhile, the impact of intra-trade trading was the lowest.